Post-translational modifications of immune checkpoints: unlocking new potentials in cancer immunotherapy - Qiongjie Hu; Yueli Shi; Huang Wang; Liuwen Bing; Zhiyong Xu (Experimental Hematology & Oncology)
Abstract Immunotherapy targeting immune checkpoints has gained traction across various cancer types in clinical settings due to its notable advantages. Despite this, the overall response rates among patients remain modest, alongside issues of drug resistance and adverse effects. Hence, there is a pressing need to enhance immune checkpoint blockade (ICB) therapies. Post-translational modifications (PTMs) are crucial for protein functionality. Recent research emphasizes their pivotal role in immune checkpoint regulation, directly impacting the expression and function of these key proteins. This review delves into the influence of significant PTMs—ubiquitination, phosphorylation, and glycosylation—on immune checkpoint signaling. By targeting these modifications, novel immunotherapeutic strategies have emerged, paving the way for advancements in optimizing immune checkpoint blockade therapies in the future.